2022
DOI: 10.7150/jca.76108
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the necessity of Pulmonary Ligament Lymph Node Dissection for Upper Lobe Stage IB NSCLC: A Propensity Score-matched Study

Abstract: Objective: The purpose of this study was to explore whether the resection of pulmonary ligament lymph nodes would affect the prognosis of patients with stage IB non-small cell lung cancer (NSCLC). Methods: We retrospectively analyzed 341 patients with upper lobe stage IB NSCLC who underwent radical surgery for lung cancer at Sun Yat-Sen University Cancer Center from 1999 to 2009. The Cox proportional hazard regression model was used to analyze the prognostic factors. After pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“… 39 However, lymph node resection is associated with a risk of chylothorax and nerve injury. 40 Our data suggested that more lymph nodes are removed by RATS, but the complications did not increase. This may be due to the flexible mechanical arm of RATS, which could reduce the hand shaking of the surgeon.…”
Section: Discussionmentioning
confidence: 54%
“… 39 However, lymph node resection is associated with a risk of chylothorax and nerve injury. 40 Our data suggested that more lymph nodes are removed by RATS, but the complications did not increase. This may be due to the flexible mechanical arm of RATS, which could reduce the hand shaking of the surgeon.…”
Section: Discussionmentioning
confidence: 54%